Exploring the Intriguing Consequences of Trauma – Pseudoaneurysm of the Tibial Arteries - Mohamad Akmal Aizat Bakhori; Ramely Rosnelifaizur; Sabrina Jane Dass; Muhammad Yunus Mohd Ramdzan; Wan Zainira Wan Zain; Md Hashim Mohd Nizam (Prague Medical Report)
Aneurysms are commonly managed by vascular surgeons, primarily affecting proximal arteries in the lower limb. In contrast, pseudoaneurysms often occur in the infrapopliteal region (Nair and Suhania, 2021), with anterior tibial artery involvement being particularly rare. It is even more uncommon for both the anterior and posterior tibial arteries to be affected simultaneously. Here, we present a case of a 21-year-old man who sustained vascular trauma to his right calf and presented one month later with difficulty in ambulation. A diagnosis of pseudoaneurysm involving both the anterior and posterior tibial arteries was made, and he successfully underwent reversed saphenous vein graft interposition for both arteries.